Development and experimental verification of self-centered y-shaped braced frame. (December 2021) - Shahiditabar, Akbar; Moharrami, Hamid
Abstract: A new type of the y-shaped (Y) bracing system composed of three brace members arranged in a y-shaped geometry, frictional mechanism for energy dissipation and pre-compressed axial springs to provide the self-centering capability is developed and studied in this paper. To improve the seismic performance of the self-centered y-shaped (SCY) braced frame, it is designed such that the structural steel members including beam, columns and braces other than the self-centering member remain within the elastic range of steel material leading to protect the structural elements from damages under lateral loading. The mechanics of this system are explained, the equations governing its hysteretic responses are outlined and scaled validation tests of two frames with different geometries are conducted under the condition of reversed cycles of loading. The results of the two tested frames under the quasi static loading show that the SCY braced frame has stable hysteretic loops which ensure a constant level of energy dissipation. Analytical findings which were verified by the results of the experimental tests show that increasing the length of the self-centering element increases the force capacity of the SCY braced frame and the self-centering element experiences the greatest deformation under lateral loading in a specific length and angle.